2018
DOI: 10.12659/msm.911454
|View full text |Cite
|
Sign up to set email alerts
|

Rab11 Functions as an Oncoprotein via Nuclear Factor kappa B (NF-κB) Signaling Pathway in Human Bladder Carcinoma

Abstract: BackgroundElevated expression of Rab11 has been reported in different human cancers, including human bladder carcinoma. This study, we investigated the biological effects and mechanism of Rab11 overexpression in human bladder carcinoma for the first time.Material/MethodsRab11 expression in bladder cancer tissues was detected using immunohistochemistry and Western blot analysis. Then, Rab11 expression was inhibited in T24 cells and it was overexpressed in BIU-87 cells. The effects of Rab11 perturbations on cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…In contrast, overexpression of Rab11a positively correlates with stage and prognosis in non–small-cell lung cancer and leads to activation of YAP, a core component of the Hippo pathway [ 77 ]. Upregulation of Rab11a has also been observed in bladder and pancreatic cancer [ 78 , 79 ]. Rab11b has recently been reported to promote breast cancer brain metastases by controlling the surface expression of β 1 integrin, which is required for successful interaction with the brain microenvironment [ 80 ].…”
Section: Dysregulation Of Endosomal Recycling In Cancermentioning
confidence: 99%
“…In contrast, overexpression of Rab11a positively correlates with stage and prognosis in non–small-cell lung cancer and leads to activation of YAP, a core component of the Hippo pathway [ 77 ]. Upregulation of Rab11a has also been observed in bladder and pancreatic cancer [ 78 , 79 ]. Rab11b has recently been reported to promote breast cancer brain metastases by controlling the surface expression of β 1 integrin, which is required for successful interaction with the brain microenvironment [ 80 ].…”
Section: Dysregulation Of Endosomal Recycling In Cancermentioning
confidence: 99%
“…Dong et al (2017) found that Rab11 promoted cell proliferation and invasion in non‐small‐cell lung cancer via the regulation of the Yes‐associated protein signaling pathway (Dong et al, 2017). Gong et al (2018) revealed that high expression of Rab11 in human bladder carcinoma promoted the growth rate and invasion of cancer cells by upregulating MMP9, cyclin E, and cyclin D1. In addition, the nuclear factor kappa B (NF‐κB) pathway was determined to mediate the regulation of Rab11 on MMP9 and cyclin D1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the nuclear factor kappa B (NF‐κB) pathway was determined to mediate the regulation of Rab11 on MMP9 and cyclin D1. Use of NF‐κB inhibitor BAY 11‐7082 partially lessened Rab11‐induced overexpression of MMP9 and cyclin D1 (Gong et al, 2018). Taken the above findings, it is advised that IFN‐γ‐reduced Rab11 expression in Schwann cells may cause DPN by inhibiting cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of activity in subunits of ESCRT complexes is often found in human cancers and has been shown to be sufficient for the development of metastatic tumours 21,22 . Elevated Rab11a expression has been observed in multiple cancers and can promote cell migration in cancerous cells of the gut, skin and breast 14,16,18 . This suggests that Rab11a, and its activators and effectors, are likely to be oncogenes.…”
Section: Discussionmentioning
confidence: 99%